Development of Severe Hyponatremia due to Salt-Losing Nephropathy after Esophagectomy for Esophageal Cancer. (28th October 2009) - Yoshioka, Katsunobu; Nishio, Minako; Sano, Soichi; Sakurai, Katsunobu; Yamagami, Keiko; Yamashita, Yoshito
Abstract : A 72-year-old woman was admitted to our hospital for esophagectomy for esophageal cancer. On the third postoperative day, she developed polyuria (3.8 L/day), massive natriuresis, hyponatremia (112 mEq/L), hyperkalemia (5.6 mEq/L), and decreased central venous pressure, which was refractory to isotonic saline infusion. Laboratory findings indicated proximal tubular injury (high urinaryβ 2 -microglobulin, coexistence of hypouricemia) together with reduced aldosterone action at the cortical collecting duct. A diagnosis of salt-losing nephropathy was made and sodium correction was done with 3% saline and fludrocortisone. She responded well to therapy. The cause of hyponatremia was considered renal tubular dysfunction together with elevated antidiuretic hormone level. Postoperatively, it is important to look for the development of salt-losing nephropathy.